Perspectives of the livestock sector in the Philippines: A review - Ortega, Arth David Sol; Mujitaba, Malam Abulbashar; Xayalath, Somsy; Gutierrez, Winson; Soriano, Ana Celina; Szabó, Csaba (Acta Agraria Debreceniensis, 2021)
The Philippine livestock industry is a vital component in the country's agricultural sector. It contributes around 18.23 percent of the gross output value in agriculture and provides livelihood to many people living in rural areas, signifying its importance with regard to the country’s economy. The constantly increasing demand for animal protein associated with the increase of the world’s population led to the intensification of livestock production, realized through the various initiatives implemented by the government, such as the import of high producing purebreds of various species. This strategy greatly influenced the country's animal genetic resource's diversity and increased food animals' population; however, it impacted the native breeds of food animals. Understanding the characteristics, performance and value of native and exotic breeds is essential to prioritize their livestock industry existence. Thus, this paper aims to characterize various native and exotic breeds of livestock in the Philippines and assess the current conservation of native animals.